2019
DOI: 10.3390/electronics8070723
|View full text |Cite|
|
Sign up to set email alerts
|

M3C: Multimodel-and-Multicue-Based Tracking by Detection of Surrounding Vessels in Maritime Environment for USV

Abstract: It is crucial for unmanned surface vessels (USVs) to detect and track surrounding vessels in real time to avoid collisions at sea. However, the harsh maritime environment poses great challenges to multitarget tracking (MTT). In this paper, a novel tracking by detection framework that integrates the multimodel and multicue (M3C) pipeline is proposed, which aims at improving the detection and tracking performance. Regarding the multimodel, we predicted the maneuver probability of a target vessel via the gated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The work of Qiauo et al [ 4 ] concentrates on unrestricted detection, tracking and re-ID of moving vessels, to recognize other vessels in their surroundings. They use a CNN-based detection model [ 5 ] and apply sensor fusion and a re-ID algorithm to achieve accurate vessel tracking in their surroundings.…”
Section: Related Workmentioning
confidence: 99%
“…The work of Qiauo et al [ 4 ] concentrates on unrestricted detection, tracking and re-ID of moving vessels, to recognize other vessels in their surroundings. They use a CNN-based detection model [ 5 ] and apply sensor fusion and a re-ID algorithm to achieve accurate vessel tracking in their surroundings.…”
Section: Related Workmentioning
confidence: 99%
“…Heyse et al developed a method of identifying marine vessels using multi-level descriptions and created a refined multi-level classifier based on deep features [22]. Qiao et al addressed ship re-identification for the long-term tracking of vessels at sea by considering each image as a set of visual cues [23]. Tian et al used a word bag model to recognize depth features [24] and demonstrated its use on a large image gallery.…”
Section: B Marine Vessel Detection and Identificationmentioning
confidence: 99%
“…32 If the influence of ship state and historical behavior are given, LSTM network will be an appropriate choice of historical sequence relevance that can remember the critical data and forget the less-important data. 33 Hence, the combination of CNN and LSTM can be taken as the self-learning framework between ship state and behavior prediction, 34 whose structure solves the key problems of uncertainty and adaptability.…”
Section: Deep Learning Network Structurementioning
confidence: 99%